The influence of roadside solid and vegetation barriers on near-road air quality. (December 2017) - Ghasemian, Masoud; Amini, Seyedmorteza; Princevac, Marko
Abstract: The current study evaluates the influence of roadside solid and vegetation barriers on the near-road air quality. Reynolds Averaged Navier-Stokes (RANS) technique coupled with the k − ε realizable turbulence model is utilized to investigate the flow pattern and pollutant concentration. A scalar transport equation is solved for a tracer gas to represent the roadway pollutant emissions. In addition, a broad range of turbulent Schmidt numbers are tested to calibrate the scalar transport equation. Three main scenarios including flat terrain, solid barrier, and vegetative barrier are studied. To validate numerical methodology, predicted pollutant concentration is compared with published wind tunnel data. Results show that the solid barrier induces an updraft motion and lofts the vehicle emission plume. Therefore, the ground-level pollutant concentration decreases compared to the flat terrain. For the vegetation barrier, different sub-scenarios with different vegetation densities ranging from approximately flat terrain to nearly solid barrier are examined. Dense canopies act in a similar manner as a solid barrier and mitigate the pollutant concentration through vertical mixing. On the other hand, the high porosity vegetation barriers reduce the wind speed and lead to a higher pollutant concentration. As the vegetation density increases, i.e. the barrier porosity decreases, the recirculation zone behind the canopy becomes larger and moves toward the canopy. The dense plant canopy with L A D = 3.33 m − 2 m 3 can improve the near-road air quality by 10% and high porosity canopy with L A D = 1 m − 2 m 3 deteriorates near-road air quality by 15%. The results of this study can be implemented as green infrastructure design strategies by urban planners and forestry organizations. Highlights: The Influence of roadside barriers on the near-road air quality was investigated. RANS technique coupled with the k − ε realizable turbulence model was utilized. Vegetation barrier depending on LAD can improve or deteriorate the air quality. The dense canopy can improve the near-road air quality by inducing vertical mixing.